Protective Effects of Amlodipine Pretreatment on Contrast-Induced Acute Kidney Injury And Overall Survival In Hypertensive Patients - Yin, Wen-jun; Zhou, Ling-yun; Li, Dai-yang; Xie, Yue-liang; Wang, Jiang-lin; Zuo, Shan-ru; Liu, Kun; Hu, Can; Zhou, Ge; Chen, Lin-hua; Yang, Hui-qing; Zuo, Xiao-cong (Frontiers in Pharmacology, 2020)
Abstract Background: Contrast-induced acute kidney injury (CI-AKI) is the most common adverse reaction caused by CM, which has been reported to prolong hospitalization and increase mortality and morbidity. The hypertensive population has proved susceptible to CI-AKI. Unfortunately, no therapeutic has been shown to prevent and cure CI-AKI effectively. A few studies have shown the protection of amlodipine on renal function, but the relationship between amlodipine and CI-AKI in hypertensive group is unknown, we aimed to study the effects of amlodipine on CI-AKI and overall survival in a large Chinese hypertensive cohort. Methods A retrospective, matched, cohort study was conducted among adults hospitalized at the Third Xiangya Hospital of Central South University from October 2007 to May 2017. CI-AKI was the primary end point of the trial, time-related all-cause mortality (including in- hospital) and length of hospital stay were the secondary end points. Propensity Score Matching was used to reduce the effect of selection bias and potential confounding. Results 868 patients with and 1798 ones without amlodipine before contrast administration were included. The incidence of CI-AKI was 10.50%. The unadjusted, adjusted and propensity‐score matched incidence of CI-AKI were lower in patients treated with amlodipine (OR, 0.650; P =0.003; OR, 0.577; P =0.007; OR, 0.687; P =0.015, respectively), and the same results were found in the subgroups of diabetes, CKD, Non-CKD, low-osmolar and elderly. Moreover, amlodipine reduced hospital stay, whether matched or not (7.08±7.28 vs 7.77±7.82, P =0.027, before matching; vs 7.81±7.58, P=0.040, after matching). 1046 patients finished follow-up including 343 amlodipine users and 703 non-users. The overall mortality was significantly lower among amlodipine users (10.79%) than controls (16.07%), the significant difference was found in survival between them (P =0.024, log-rank test), amlodipine was associated with longer overall survival (HR, 0.623; 95% CI [0.430-0.908], P =0.014). Conclusion: In conclusion, we first found amlodipine treatment before contrast exposure played a role in protecting hypertensive patients from CI-AKI and prolonging survival.